2017
DOI: 10.4103/1817-1737.203746
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of obstructive sleep apnea syndrome in a Saudi Arabian population

Abstract: BACKGROUND:Obstructive sleep apnea (OSA) is a common disorder worldwide; however, epidemiological studies on its prevalence lack in Saudi Arabia. This study aimed to determine the prevalence and risk factors of OSA in Saudi Arabia.METHODS:The study was performed from 2013 to 2015 in two stages. The screening stage was first; a random sample of Saudi employees (n = 2682) 30–60 years of age completed a survey that included the Wisconsin questionnaire. According to these data, the subjects were categorized as hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
62
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 42 publications
11
62
3
Order By: Relevance
“… 3 Based on a study in Saudi population, it has been reported that nearly 4.0% of adult males and 1.8% of adult females are affected by OSA. 4 Evaluating the risk of OSA among Saudi population, not only was it found to be similar to that reported in Western societies, but also one out of 3 Saudi males and 4 out of 10 Saudi females are at high risk of developing OSA. 4 - 6 Unfortunately, moderate to severe OSA still remains undiagnosed in 93% of women and 82% of men around the globe.…”
supporting
confidence: 54%
See 1 more Smart Citation
“… 3 Based on a study in Saudi population, it has been reported that nearly 4.0% of adult males and 1.8% of adult females are affected by OSA. 4 Evaluating the risk of OSA among Saudi population, not only was it found to be similar to that reported in Western societies, but also one out of 3 Saudi males and 4 out of 10 Saudi females are at high risk of developing OSA. 4 - 6 Unfortunately, moderate to severe OSA still remains undiagnosed in 93% of women and 82% of men around the globe.…”
supporting
confidence: 54%
“… 4 Evaluating the risk of OSA among Saudi population, not only was it found to be similar to that reported in Western societies, but also one out of 3 Saudi males and 4 out of 10 Saudi females are at high risk of developing OSA. 4 - 6 Unfortunately, moderate to severe OSA still remains undiagnosed in 93% of women and 82% of men around the globe. 1 , 3 Furthermore, undiagnosed OSA has been identified as an independent predisposing factor for early development of chronic cardiovascular, endocrine or neurological comorbid conditions.…”
supporting
confidence: 54%
“…Moreover, mild OSA is estimated to be in approximately 14% of men and 5% of women [7] . A recent local study done by Wali et al [8] show an estimate of 12.8% in men and 5.1% in women for the overall prevalence of OSA in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 94%
“…Epidemiological studies from Asia have shown that the prevalence of OSA in patients with hypertension varies from 14-75% (Ip et al, 1999;Pensuksan et al, 2014;Shirani et al, 2016;Wali, et al, 2017). A number of studies from India have garnered data regarding the overall prevalence of OSA in general population (Kumar et al, 2006;Reddy et al, 2009;Sharma et al, 2010;Udwadia et al, 2004).…”
Section: Introductionmentioning
confidence: 99%